Green marketing and its implications for consumers and businesses in Malaysia - Lee, Gerald C. P.; Ahmad, M. I. (Academy of Marketing Science, 1997)
Environmental issues are fast becoming important business issues m Malaysia. Many corporations are beginning to incorporate ‘green values’ into their marketing strategies. Malaysian consumers have been slow in responding to the environmental issues in the past but with increased per capita income and higher educational levels, the tide is now changing rapidly. This study was undertaken to assess the level of understanding of the concepts of green marketing and green products among consumers and marketers in Malaysia. The research also evaluated the ‘green corporations’ and their role and responses to the green revolution.